2020
DOI: 10.1177/0093854820932204
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Pretrial Risk Assessment: An Examination Across Role in the Initial Pretrial Release Decision

Abstract: Pretrial risk assessments are used to inform pretrial release decisions by judicial officers and criminal justice entities. Existing research indicates that negative perceptions of risk assessment can interfere with adherence to the tool. Although perception plays an important role in the implementation of pretrial risk assessment, little is known about what those involved in the initial pretrial release decision—including pretrial officers, judges, prosecutors, and defense attorneys—think about this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…To demonstrate, a study of the Risk and Needs Triage (RANT; Public Health Management Corporation Research & Evaluation Group, n.d.) showed no racial differences in RANT risk scores or their predictive validity but did show that Black people were detained pretrial for about 2 weeks longer than white people with similar risk scores, charges, and criminal histories (Marlowe et al, 2020). Furthermore, pretrial court actors have self-reported varying levels of support for and willingness to use pretrial risk assessment instruments to aid their recommendations and decisions (DeMichele et al, 2019;Terranova et al, 2020). Advocates, researchers, and tool developers alike have suggested that making changes to how results are presented to pretrial court actors may increase alignment between pretrial risk assessment results and release recommendations, thereby supporting the goals of pretrial reform, including reduced detention rates and more racially equitable release decisions (Advancing Pretrial Policy and Research, n.d.;The Leadership Conference on Civil and Human Rights, 2018).…”
Section: Pretrial Risk Assessmentmentioning
confidence: 99%
“…To demonstrate, a study of the Risk and Needs Triage (RANT; Public Health Management Corporation Research & Evaluation Group, n.d.) showed no racial differences in RANT risk scores or their predictive validity but did show that Black people were detained pretrial for about 2 weeks longer than white people with similar risk scores, charges, and criminal histories (Marlowe et al, 2020). Furthermore, pretrial court actors have self-reported varying levels of support for and willingness to use pretrial risk assessment instruments to aid their recommendations and decisions (DeMichele et al, 2019;Terranova et al, 2020). Advocates, researchers, and tool developers alike have suggested that making changes to how results are presented to pretrial court actors may increase alignment between pretrial risk assessment results and release recommendations, thereby supporting the goals of pretrial reform, including reduced detention rates and more racially equitable release decisions (Advancing Pretrial Policy and Research, n.d.;The Leadership Conference on Civil and Human Rights, 2018).…”
Section: Pretrial Risk Assessmentmentioning
confidence: 99%
“…Additional findings from the implementation science literature nicely complement the above, and provide some additional context for understanding why PRAI usage may not have the intended effect. In particular, multiple studies suggest that there is variability across courtroom workgroup members in the extent to which PRAIs are valued and/or contribute to recommendations (DeMichele et al., 2019; Terranova et al., 2020). Some of this has been attributed to the different roles of courtroom workgroup members, as well as a certain degree of misunderstanding of the tools’ intended use.…”
Section: The Place Of Prais In Ongoing Bail Reform Effortsmentioning
confidence: 99%
“…La existencia de tales sesgos explica que en numerosas ocasiones la opinión pública ponga en duda la imparcialidad de los jueces y el resto de los operadores jurídicos al tomar sus decisiones. De hecho, el impacto que esta forma de proceder de la mente humana tiene en las decisiones jurídico-penales se aprecia, aún más, con la llegada del EBS, pues los estudios realizados hasta el momento (y que serán analizados en mayor profundidad a continuación) reflejan cómo los jueces estadounidenses no están teniendo en cuenta los resultados arrojados por las herramientas (Stevenson y Doleac, 2018;Stevenson y Doleac, 2019;Terranova et al, 2020;Garret y Monahan, 2020). Consecuentemente, en lugar de conseguir que las decisiones judiciales sean más objetivas y precisas gracias a la información aportada por las HVR, los jueces siguen decidiendo en base a su particular experiencia y a sus propios criterios que, en ningún caso, están libres de sesgos.…”
Section: A) La Existencia De Sesgos En Los Juecesunclassified
“…En efecto, los algoritmos pueden permitir una toma de decisiones eficiente, optimizada y basada en datos (Kyung Lee, 2018). Esta visión optimista ha impulsado la adopción de algoritmos para la toma de decisiones en multitud de ámbitos de nuestra sociedad, como en el campo de los negocios (Siegel, 2016), en la salud (Jee et al, 2013), en la educación (Selwyn, 2015;Baker, 2016), en la política (Kim et al, 2014) y, poco a poco, también en la justicia y la organización penitenciaria (Botnick, 2015;Kehl et al, 2017;Stevenson y Doleac, 2018, 2019Scurich y Krauss, 2019;McKay, 2019;De Michele et al, 2019;Garret y Monahan, 2020;Terranova et al, 2020). La irrupción de este fenómeno está trasformando radicalmente el funcionamiento tradicional de nuestra sociedad y, aunque las ventajas son innegables, también los son las consecuencias negativas derivadas del uso de esta tecnología.…”
Section: Percepciones Ciudadanas En Torno a Las Decisiones Algorítmic...unclassified